1984
DOI: 10.1099/0022-1317-65-8-1405
|View full text |Cite
|
Sign up to set email alerts
|

Multiple JC Virus Genomes from One Patient

Abstract: SUMMARY JC virus was previously isolated from the urine and from diseased brain of a patient with progressive multifocal leukoencephalopathy. The DNAs of these isolates, MAD-7 and MAD-8 respectively, were shown in this study to be mixtures of several different full-length genomes. By differences in their restriction endonuclease cleavage patterns, the genomes were categorized into two types. Type I DNA was defined as that typified by the prototype virus, MAD-l; Type II, that typified by viral DNA molecularly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Since we find these sites to be in full agreement with type-determining sites in the V-T intergenic region, it is clear that the RFLP-based Types A and B of Yogo et al (1991) correspond to our Types 1 and 2, respectively. However, typing which is not based on known sequence variation tends to be ambiguous, making it difficult to include additional isolates (Grinnell et al, 1983b;Martin & Foster, 1984;Yogo et al, 1991;Takahashi et al, 1992;Tominaga et al, 1992). Using our simple system of type-determining sites, new sequences can be easily classified relative to known strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we find these sites to be in full agreement with type-determining sites in the V-T intergenic region, it is clear that the RFLP-based Types A and B of Yogo et al (1991) correspond to our Types 1 and 2, respectively. However, typing which is not based on known sequence variation tends to be ambiguous, making it difficult to include additional isolates (Grinnell et al, 1983b;Martin & Foster, 1984;Yogo et al, 1991;Takahashi et al, 1992;Tominaga et al, 1992). Using our simple system of type-determining sites, new sequences can be easily classified relative to known strains.…”
Section: Discussionmentioning
confidence: 99%
“…Classification schemes based on the structure of the regulatory region have been described (Martin et al, 1985;Walker & Frisque, 1986), but it is not clear whether the patterns of sequence rearrangement reflect the genotype of the virus or result from host cell biology. Similarly, typing by restriction fragment length polymorphism (RFLP) (Yogo et al, 1990;Grinnell et al, 1983a, b;Martin & Foster, 1984) has not revealed the kind of clear-cut taxonomy which could lead to simple and unambiguous typing. In general, RFLP typing is a low resolution analysis which misses many informative sequence changes, and leaves doubt as to the actual sequence variations at the sites altered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that JCV may persist in the kidney in a form termed archetype Bog0 et al, 19901. During the long term immunosuppressive condition, the virus may be reactivated and may rearrange its promoter-enhancer regulatory region by deletion and/or duplications to form different strains and cause PML in brain [Chuke et al, 1986;Dorries, 1984;Frisque et al, 1984;Martin and Foster, 1984;White et al, 19921. This speculation could be correlated with the fact that about 5% of AIDS patients succumb to PML [Berger et al, 1987;Krupp et al, 1985;Kure et al, 1991;Snider et al, 19831. Patients with various autoimmune diseases, such as systemic lupus erythematosus (SLE), Sjogren's syndrome (SS), rheumatoid arthritis (RA), or dermatomyositis/polymyositis (DMIPM), primarily become immunocompromised because of intrinsic abnormalities of the immune system, or immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3C), is more typical of NCCR variants found in PML patients than Mad-1. This variant contains a repeat structure similar to that of the prototype, with one large deletion and one insertion, as well as several smaller insertions and base changes (316,317). Examples of rearranged NCCRs can be found in many studies that have sequenced, annotated, and aligned multiple NCCRs from PML patients (413,485,552,557).…”
Section: Analysis Of the Viral Genomementioning
confidence: 99%